MODERN TECHNOLOGIES, CHALLENGES AND PROSPECTS FOR CREATING ANALOGUES OF MEAT PRODUCTS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents the results of analytical research on the current state and features of technologies for the production of meat analogs. The relevance and advantages of such products, including environmental sustainability, ethics, potential safety, variability of ingredients and flavor profiles, are noted. It is determined that vegetable and cultured meat have potential, but also certain disadvantages and prospects for technology development. The key ingredients of meat product analogs and their functions in the technological system are characterized. It is determined that the key technological challenges in the production of meat analogues are the reproduction of the structure of native meat, its color, taste, aroma, and nutritional properties.The problematic elements for further research are identified, in particular, the existing gap between analogs and real meat in terms of texture, color, taste, aroma, and nutritional properties. It is noted that mixing and blending of various plant materials to obtain functional properties is currently an actual practice. In this case, the emphasis should be on functionality for use in meat analogs, rather than on classical functionality such as purity and solubility. Another direction is to explore new protein sources and structuring technologies. Studying the interaction of components is also crucial for the development of meat analog technologies.In terms of texture, an important area of research is the transformation of plant globular proteins into fibrillar structures, the use of dietary carbohydrates to increase the viscosity and pseudoplasticity of meat analogues, and the use of a fatty component of plant origin (solid, liquid oils or their blends) to form the structure.It is also important to take into account the amino acid profiles of different protein sources and incorporate a variety of protein sources, implement appropriate approaches to increase the nutritional value of meat analogues and reduce losses during production, take into account the problem of imitating meat flavor and aroma, which is to reproduce the complex flavor profile of meat, and achieve the appropriate meat color.
Keywords: analog; meat products; technology; vegetable proteins